How Should Subnational Government Borrowing Be Regulated? : Some Cross-Country Empirical Evidence - Plekhanov, Alexander (IMF Working Papers; Working Paper ;, 2005)
Countries have adopted various institutional responses to subnational government borrowing. Using a sample of 44 countries 1982-2000, this paper provides a panel data analysis to determine the most effective borrowing constraints for containing local fiscal deficits. The results suggest that no single institutional arrangement is superior under all circumstances. The appropriateness of specific arrangements depends upon other institutional characteristics, particularly the degree of vertical fiscal imbalance, the existence of any bailout precedent, and the quality of fiscal reporting.